2020
DOI: 10.1055/a-1139-9200
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine, Metabolic and Pharmacological Effects of Thyronamines (TAM), Thyroacetic Acids (TA) and Thyroid Hormone Metabolites (THM) – Evidence from in vitro, Cellular, Experimental Animal and Human Studies

Abstract: Thyroid hormone metabolites (THM) with few or no iodine substituents such as 3,5-T2, the thyronamines 3-T1AM and T0AM, and their oxidation products, the thyroacetic acids (TA) formed by monoamine oxidases, have recently attracted major interest due to their metabolic actions which are in part distinct from those of the classical thyromimetic hormone T3, the major ligand of T3 receptors. This review compiles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 107 publications
1
11
0
Order By: Relevance
“…Limitations of our approach are in the comparably small sample size and in the fact that subjects were recruited based on routine investigations, so that we were unable to determine non-classical thyroid hormones including 3,5-diiodothyronine (3,5-T2), thyronamines and iodothyroacetates, which may have a strong impact on cardiovascular physiology ( 42 44 ). Furthermore, our ECGs were not obtained digitally so that automatic measurements with a higher accuracy than the manual method could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of our approach are in the comparably small sample size and in the fact that subjects were recruited based on routine investigations, so that we were unable to determine non-classical thyroid hormones including 3,5-diiodothyronine (3,5-T2), thyronamines and iodothyroacetates, which may have a strong impact on cardiovascular physiology ( 42 44 ). Furthermore, our ECGs were not obtained digitally so that automatic measurements with a higher accuracy than the manual method could not be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated TH research requires the development of methods for a comprehensive determination of TH and its metabolites in human and murine samples as well as in samples from in vitro studies. These methods were substantially refined and evaluated by Köhrle and his team and led to a considerable number of analytical applications in cell cultures, animal models and large epidemiological cohorts by groups of the TTA consortium [3][4][5][6]. TH synthesis is regulated by the hypothalamic-pituitary-thyroid axis.…”
Section: Determination and Action Of Thyroid Hormonesmentioning
confidence: 99%
“…Besides the classical hormones T3 and T4, the biochemical properties and modes of action of new TH metabolites such as 3-iodothyronamine, thyroacetic acid or 3,5-diiodothyronine [20,21] at membrane receptors have been investigated by the Biebermann group [22,23] and at transient receptor potential channels by Mergler and team [24], in addition to first mouse and cohort analyses, hinting to a potential cardiometabolic relevance [4][5][6]25]. Unravelling the molecular basis of TH action at the level of target cells and tissues is crucial for an individualised TH replacement strategy and hereby comparative studies using rodent and human samples are helpful to identify reliable biomarkers as demonstrated by the groups of Mittag and Brabant [26].…”
Section: Thyroid Hormone Metabolites and Their Actionmentioning
confidence: 99%
“…Thyronamines (TAMs), speculated to derive from thyroid hormones (TH) through deiodination and decarboxilation, represent a novel class of signaling molecules detected in several mammal tissues, including brain, liver, pancreas and human plasma [1,2]. Among them, 3-iodothyronamine (T1AM), discovered in 2004 as the most potent agonist of traceamine associated receptor type 1 (TAAR1) [2], has extensively been studied for almost two decades, revealing to be endowed with a wide range of bio-pharmacological properties, including metabolic reprogramming and neuroprotection [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%